Duodenal lymphangitis carcinomatosa: A rare case - Ilanchezhian Subramanian, MBBS, MD; Prabhu Radhan, MBBS, MD; Rajoo Ramachandran, MBBS, MD; Rajamani Anand, MBBS; Venkata Sai, MBBS, DMRD, DNB, PhD; Rajendiran Swaminathan, MBBS, MD (Radiology Case Reports, 2014)
Duodenal lymphangitis carcinomatosa has been sporadically described, and little attention has been paid so far. To our knowledge, no data on radiological findings for this rare entity has been published. We report a case of duodenal lymphangitis carcinomatosa secondary to gallbladder mass in a 44-year-old Indian man to focus on the radiological diagnosis, which was further confirmed by endoscopic-guided biopsy and immunohistochemical analysis.